Protective Effect of Pituitary Adenylate Cyclase-Activating Polypeptide-38 Against Radiation-Induced Myocardial Injury in Mice - Li, Huan; Yi, Pei-Qiang; Zhu, Qian; Cao, Lu; Xu, Cheng; Li, Min; Chen, Jia-Yi (Cardiology and Cardiovascular Medicine, 2023)
Background: Radiation-Induced Heart Disease (RIHD) restricts the survival benefit of radiotherapy for thoracic tumors. Myocardial fibrosis and remodeling are late consequences of the long-term development of RIHD, and pituitary adenylate cyclase-activating polypeptide-38 (PACAP38) could ameliorate RIHD. Methods: An animal model of heart irradiation was prepared from mice, and subjected to X-ray exposure. Mice were pretreated with PACAP38 in vivo before cardiac irradiation. The cardiac function and pathological changes of myocardium were evaluated by animal echocardiography, micro PET-CT and histological staining, respectively. Results: Murine heart exposed to a single dose of 20 Gy X-ray resulted in a significant increases pathological injury and average standard uptake value (SUV) of 18F-FDG induced by irradiation in mice. The cardiac function that displays systolic parameter LVEF and diastolic parameter E/e' of mice did not change significantly after irradiation at 6 months. PACAP38 (10 μg/100μl, i.p.) significant inhibited the increase of average SUV of 18F-FDG as well as myocardial pathological damage induced by irradiation. The average SUV in the irradiated area of the heart in the control group and irradiation group were 0.76±0.04 and 1.20±0.07, respectively (P<0.05). While in the PACAP38 treatment group, the average SUV decreased to 0.86±0.06 (PACAP38+IR vs. IR, P<0.05), indicating that PACAP38 effectively protected heart function against radiation-induced heart injury. Conclusions: Our data reveal that PACAP38 significantly alleviated the myocardial fibrosis, remodeling and metabolic dysfunction induced by radiation exposure of heart. The cardioprotective role of PACAP38 provide a new sight for possible intervention of RIHD.